TERRACE: A Program to Calculate Terrain Correction Using Hammer Chart in Gravity Data Processing - Rochmah, Dwi Febriana; Susilo, Adi; Wasis, Wasis (Physics Student Journal, 2014)
Surface irregularities in the vicinity of gravity station can exert upward or downward pull on the gravity meter. To obtain better data, geophysicists use terrain correction to reduce topography effect toward gravity measurement. Terrain correction in gravity data processing was done by applying Hammer Chart into topographic maps. This method is inefficient because it is done manually and tends to be subjective. TERRACE program has developed as a program to define inner (r1) and outer (r2) sectors radii by superimposing Hammer Chart over a topographic map. The calculation of terrain corrections are resulted automatically, saved as TC1.txt. Verification result has done by the comparison between terrain calculation from Geosoft Montaj and TERRACE program. This program has shown the terrain correction results over 9 observation points from 6x6 km2 area at Tiris village, Probolinggo Regency, East Java Province has value range of 0.3077-0.8724 mGal.